Catalytic dye degradation by novel phytofabricated silver/zinc oxide composites - Bloch, Khalida; Mohammed, Shahansha M.; Karmakar, Srikanta; Shukla, Satyajit; Asok, Adersh; Banerjee, Kaushik; Patil-Sawant, Reshma; Mohd Kaus, Noor Haida; Thongmee, Sirikanjana; Ghosh, Sougata (Frontiers in Chemistry, 2022)
Phytofabrication of the nanoparticles with exotic shape and size is an attractive area where nanostructures with noteworthy physicochemical and optoelectronic properties that can be significantly employed for photocatalytic dye degradation. In this study a medicinal plant, Plumbago auriculata leaf extract (PALE) was used to synthesize zinc oxide nanoparticles (ZnONPs) and silver doped zinc oxide nanoparticles (ZnOAg1NPs, ZnOAg10NPs, ZnO10Ag1NPs) by varying the concentration of the metal precursor salts, i.e. zinc acetate and silver nitrate. The PALE showed significantly high concentrations of polyphenols, flavonoids, reducing sugar, starch, citric acid and plumbagin up to 314.3±0.33 µg/mL, 960 ± 2.88 µg/mL, 121.3 ± 4.6 µg/mL, 150.3± 3.17 µg/mL, 109.4±2.36 µg/mL, and 260.4 ± 8.9 µg/mL, respectively which might play an important role for green synthesis and capping of the phytogenic nanoparticles. The resulting nanoparticles were polydispersed which were mostly irregular, spherical, hexagonal and rod like in shape. The pristine ZnONPs exhibited a UV absorption band at 352 nm which shifted around 370 in the Ag doped ZnONPs with concomitant appearance of peaks at 560 nm and 635 nm in ZnO10Ag1 and ZnOAg1NPs, respectively. The majority of the ZnONPs, ZnOAg1NPs, ZnOAg10NPs, and ZnO10Ag1NPs were 407 nm, 98.3 nm, 231 nm, and 90 nm in size, respectively. Energy dispersive spectra confirmed the elemental composition of the nanoparticles while Fourier transform infrared spectra showed the involvement of the peptide and methyl functional groups in the synthesis and capping of the nanoparticles. The nanocomposites exhibited superior photocatalytic degradation of methylene blue dye, maximum being 95.7% by the ZnOAg10NPs with a rate constant of 0.0463 s-1 following a first order kinetic model.